Enabling dynamic spectrum access for cognitive radio using software defined radio platform - A. Rashid, Rozeha (2011)
This Spectrum occupancy measurement in many countries shows sporadic and poorly utilized licensed radio spectrum due to the outdated exclusive spectrum access policy. Dynamic Spectrum Access (DSA) technique allows cognitive (unlicensed) user (CU) to opportunistically transmit in a primary (licensed) user (PU) frequency band for a given time if it does not detect any ongoing operations. In this work, DSA is realized using cognitive radio (CR) technology due to its features of able to sense, learn, adapt and react according to the environment. The proposed design of the DSA based CR system consists of four main functional blocks: spectrum sensing, spectrum management, spectrum decision and data transmission. The implementation is done using GNU Radio and Universal Software Radio Peripheral (USRP) Software Defined Radio (SDR) platform. The result shows a significant improvement in term of Packet Reception Rate (PRR) in DSA based CR systems compared to the system without DSA capability.